FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ADOPSI INOVASI PENGGUNAAN PUPUK MAJEMUK DI KECAMATAN BAKI KABUPATEN SUKOHARJO - Asifah Mariana; Sutarto Sutarto; Bekti Wahyu Utami (Universitas Sebelas Maret, 2006)
This research is conducted to investigate all factors that related to the adoption of the innovation in utilizing complex fertilizer, to investigate the adoption 's level of the innovation done by the farmer in utilizing complex fertilizer, and to investigate the relation between the factors that related to the adoption of the innovation in utilizing complex fertilizer in Baki, Sukoharjo. The basic method used in this research is descriptive method with the technique of survey. The research's location is determined through purposive, in other words, Baki - Sukoharjo is chosen based on the consideration that this area has the most high level on producing rice. There are 40 respondents taken as the sample through simple random sampling. To identify all factors that related to the adoption of the innovation in utilizing complex fertilizer and to measure the level of the adoption on that innovation, the utilizing of the complex fertilizer is counted according to intervel-width formula, while to identify the relationship between those factors, the researcher used the Spearman-rank correlation test (rs). The result shows us that the majority of the farmers are above 50 years of age (> 50), 45 percent of them have a formal education either graduated/non-graduated from senior high school (SLTA), 50 percent of then have been joined non-formal education at least 1-2 times, 47,5 percent of them have 0,5-1 Ha area as their agriculture business, their majority of their salary is in the category of well-to-do and able to saving it, their economy environment is in the category of supporting and least supporting, their social environment is in the category of non-supporting and their innovation action in using the complex fertilizer is in the category of wellproper used. In the level of 95 percent trustworthy, there is a significant relationship between formal educations, width of the agriculture business area, economy environment, and innovation characteristics with the adoption of the innovation in utilizing complex fertilizer. Whereas, age, nonformal education, salary, and social environment are not having a significant relationship with the adoption of the innovation in utilizing complexfertilizer in Baki, Sukoharjo.